Brightly Luminescent and Color-Tunable CsPbBr3 Nanocrystals with Enhanced Stability and Room Temperature Cubic Structure through Codoping with MnCl2 - Darwish, Elshaimaa; Elia, Jack; Fehn, Dominik; Köllner, David; Pourjafar, Amir; Christiansen, Silke; Meyer, Karsten; Webber, Kyle Grant; Brabec, Christoph; Batentschuk, Miroslaw; Osvet, Andres (Advanced Engineering Materials, 2024)
Lead halide perovskites have attracted much attention from the scientific community in recent years due to their attractive properties and their proven potential in many applications. Nevertheless, their stability and lead toxicity have remained a problem. Herein, the potential of manganese as a divalent dopant to offer better stability and replace a fraction of the toxic lead ions is investigated. Moreover, the reverse microemulsion method is used to obtain tunability in emission and bandgap by doping cesium lead bromide. Furthermore, cubic cesium lead bromide particles are managed to obtain at room temperature as a result of doping.
CRIS-Team Scopus Importer:2024-05-24
Keywords: light conversion; perovskite nanoparticle; semiconductor quantum dots

Exploring the Effect of Polymer Addition to the Room Temperature Synthesis of Colloidal Lead Halide Perovskite for Better Stability, Higher Passivation, and More Uniform Particle Size - Darwish, Elshaimaa; Elia, Jack; Batentschuk, Miroslaw; Osvet, Andres; Brabec, Christoph (Advanced Engineering Materials, 2025)
In recent years, metal halide perovskites have emerged as a promising alternative to existing semiconductor materials in many applications due to its appealing properties. Despite perovskite huge potentials in many applications, they are still suffering from different kinds of stability issues that are hindering their marketability. Several attempts to stabilize perovskites including polymer encapsulations and inclusions of perovskite materials into polymer matrices due to the stability against moisture that the polymer can offer. Nevertheless, the polymer is acting as an unreactive component without any role into enhancing the optical properties of the studies metal halide perovskite. This study examines the incorporation of the polymer BUTVAR (polyvinyl butyral [PVB]) in the production of various perovskite structures at room temperature: CsPbBr3, Cs2PbBr5, FAPbBr3, and MAPbBr3. The study demonstrates that the incorporation of the polymer solution enhances the optical characteristics and improves the shape uniformity of the resultant perovskite material without altering the inherent structure of the original perovskite material. Furthermore, it improves the durability of the acquired particles against UV irradiation.
CRIS-Team Scopus Importer:2025-04-11
Keywords: perovskite nanocrystals; perovskite nanoparticles higher passivation; perovskite stability; polymer addition to perovskite nanocrystal synthesis; room temperature synthesis

Modified Synthesis of Cs4PbBr6 for Enhanced Purity and Quantum Yield and for Exploring Its Potential as a High Stokes Shift Material for Down-Conversion in Solar Cells - Darwish, Elshaimaa; Elia, Jack; Barabash, Anastasia; Hu, Huiying; Batentschuk, Miroslaw; Osvet, Andres (Advanced Engineering Materials, 2024)
Energy demands have kept increasing in recent years due to expanding human activity. Silicon solar cells offer an attractive renewable energy source while their external quantum efficiency (EQE) can still be enhanced; one way of doing this is by applying a photon energy downshifting layer. Herein, Cs4PbBr6 is applied as a downshifting layer; the Cs4PbBr6 is synthesized in the form of colloidal nanoparticles, and several modifications are introduced to the synthesis process, resulting in the enhancement of the photoluminescence quantum yield, improving the particle size distribution and reducing the CsBr impurities which appear as a side product during the synthesis of Cs4PbBr6. The application of the produced modified particles in the form of thin films on the top of Si solar cells shows an enhancement of the (EQE) of the solar cells when compared to the unmodified particles.
CRIS-Team Scopus Importer:2024-06-07
Keywords: 0D Cesium lead halide; down conversion; enhancing quantum yield; perovskite nanoparticles; silicon solar cells